Program for biosafety systems: A partnership program for biosafety capacity development - International Food Policy Research Institute (International Food Policy Research Institute, 2007)
The likelihood of transgenic plants causing harm to the environment or to human health has led to the development of regulatory regimes that are specifically applied to assessing the biosafety of these products. Development of an effective biosafety system is important to protect consumers and the environment as well as to ensure safe access to new products and technologies developed in-country or elsewhere. The Program for Biosafety Systems (PBS) addresses these challenges through an integrated program of research, capacity development, and outreach.